Cytological Distinctions Between Timun Suri and Cucumber Discovered by Fluorescence In Situ Hybridization (FISH) Using 45S Ribosomal DNA Gene - Agus Budi Setiawan; Aziz Purwantoro; Ari Wibowo (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
The genus Cucumis including timun suri, melon and cucumber, is an important horticultural crop of flowering plants. The dispute of timun suri terminology is leading to false-positive results in the nomenclature of timun suri in Indonesia. Although molecular research on these species has been widely conducted, detailed information and precise evidence based on the molecular cytogenetic approach are poorly investigated. The FISH technique was applied to reveal the cytological distinctions among these species. Here, this research conducted physical mapping of 45S ribosomal DNA (rDNA) on six accessions of Cucumis. The chromosome number of cucumber is 14 chromosomes, while timun suri and melon are 24 chromosomes. The number of 45S rDNA loci in cucumber, melon and timun suri was highly conserved. All cucumber accessions in this study had nine to ten 45S rDNA loci with strong and weak signal intensities located at proximal regions of the short arms. In melon and timun suri the signals of two pairs of 45S rDNA were located at the terminal and interstitial regions of the short arms. These were clear shreds of evidence to confirm that timun suri was cytogenetically closed to melon instead of cucumber. It confirmed that timun suri cannot be classified as a cucumber